2020
DOI: 10.1136/openhrt-2020-001339
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcomes of mitral valve surgery in France in the recent era: a nationwide perspective

Abstract: ObjectivesUnbiased information regarding the surgical management of patients with mitral regurgitation (MR) at the nationwide level are scarce and mainly US-based. The Programme de Médicalisation des Systèmes d’Information, a mandatory national database, offers the unique opportunity to assess the presentation and outcomes of all consecutive mitral valve (MV) surgeries performed in France in the contemporary era.MethodsWe collected all MV surgeries performed for MR in France in 2014–2016. MR aetiology was clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…The French national database reported that the in-hospital mortality rates of patients with isolated valve surgery for SMR were 2.2% after MVP and 7.1% after MVR. 14) Importantly, transcatheter intervention was performed at the same rate as MVP according to the Euro Heart Survey II (32.2%). 8) A report from The Society of Thoracic Surgeons Adult Cardiac Surgery Database from 2011 to 2016 indicated that only 4.2% and 1.3% of mitral valve surgeries were for SMR and IMR, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The French national database reported that the in-hospital mortality rates of patients with isolated valve surgery for SMR were 2.2% after MVP and 7.1% after MVR. 14) Importantly, transcatheter intervention was performed at the same rate as MVP according to the Euro Heart Survey II (32.2%). 8) A report from The Society of Thoracic Surgeons Adult Cardiac Surgery Database from 2011 to 2016 indicated that only 4.2% and 1.3% of mitral valve surgeries were for SMR and IMR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to the French national database between 2014 and 2016 and the Euro Heart Survey II, SMR was observed in 16.2% and 24.3% of patients who underwent mitral valve surgeries, with in-hospital mortality rates of 7.8% and 4.9%, respectively. 8 , 14) Recently, surgeons are more reluctant to perform MVP for 38.9% and 36.8% of patients with SMR, respectively. The French national database reported that the in-hospital mortality rates of patients with isolated valve surgery for SMR were 2.2% after MVP and 7.1% after MVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, all patients with rheumatic valvular disease underwent replacement in this study 20 . The vast majority of the rheumatic patients included in our manuscript underwent mitral valve replacement—this has been identified as an independent risk factor for increased LOS (vs. mitral valve repair) 21,22 . It is notable that despite this increased LOS, there was no difference in hospital cost between groups.…”
Section: Commentmentioning
confidence: 92%
“…20 The vast majority of the rheumatic patients included in our manuscript underwent mitral valve replacement-this has been identified as an independent risk factor for increased LOS (vs. mitral valve repair). 21,22 It is notable that despite this increased LOS, there was no difference in hospital cost between groups. We have previously identified complications as drivers of hospital cost, and the additional non-ICU care for rheumatic patients should be accounted for in term of expected resources but may not have a meaningful impact of hospital cost.…”
Section: Commentmentioning
confidence: 97%